Research on the MPA Education and Training Model with Internal Structure; Teaching Perspective as the Core and Double Loop; as the Main Body (Global Journal of Human-Social Science, 2023)
Over the past two decades China s MPA education has undergone a transformation from high-speed development to high-quality development However there are still problems and challenges in the current development of MPA education in China In the new era MPA education should take the opportunity of comprehensive improvement and innovation of education to reform its teaching and innovate its training methods Change the traditional external transmission teaching perspective and build a internal structure teaching perspective with a dynamic knowledge perspective a proactive student perspective and an active learning perspective as the core Give full play to the joint efforts of schools government and society and form a double loop talent training model that integrates theoretical knowledge and management practice Promote MPA students to achieve research-based learning cooperative learning social learning and innovative learning enhance the quality of talent cultivation and help to achieve a new realm of Chinese governance
Keywords: MPA education; inner constructivism teaching view